Urgensi Sila Pertama Pancasila Dalam Perkembangan Teknologi - San Mikael Sinambela; Yakobus Ndona (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research was conducted with the aim of determining the urgency of the first principle of Pancasila in technological developement in the current era of increasingly rapid globalization. This research method is to use a descriptive qualitative method with a literature study approach. The results of this reseacrh show that the first principles of Pancasila is very important yo implement in the curret technological era because many people are increasingly turning to the existence of God and think that technology has more influence and impact on their lives and also so that people maintain positive ethics and behavior in carrying out their daily activities. In conclusion, the Indonesian government must always socialize the importance of the first principle of Pancasila to be applied to society, so that there is no erosion of ethics and the rise of negative actions in society.